Results of the Olfactory Cognition Test Performed on 45 Female University Students (Global Journal of Medical Research, 2020)
The sense of smell is related to the quality of life and not only can protect oneself from dangers such as food poisoning, gas leakage, and fire. But also various pleasures such as enjoying a delicious meal and the scent of flowers. This time, we report that we conducted an olfactory cognitive test using open essence on healthy 45 female university students. The Open Essence (made by FUJIFILM) has the smell as same as the odor Stick Identification Test (OSIT-J). The aromas used in the open essence includes curry, perfume, Japanese cypress, India ink, menthol, rose, wood, stinky socks/sweat, roasted garlic, condensed milk, gas for cooking, and Japanese mandarin aromas. This 12 different odorants perception is not necessarily culture-free; the Japanese version employed. Depending on the type of odor, some of them were difficult to understand, and some that were easy to understand. The most willrecognized odor was the smell of stinky socks/sweat, and the most hard to understand odor was mandarin orange. In the future, it is necessary to individually examine not only the number recognized in the olfactory recognition test but also the odor that was understand.
Keywords: olfaction test; open essence; cognition; female; university student